IMPLEMENTATION FEASIBILITY OF ENTERPRISE FINANCIAL CONTROLLING - Olena Golovko; Nataliya Tretiak; Kateryna Oriekhova (Соціальна економіка)
In modern economic conditions, in order to ensure the viability of entrepreneurial activity, it is necessary to apply a high degree of rationality and systematicity in the management of own and borrowed financial resources. Enterprises must skillfully determine their strategy and tactics of actions on the market, carefully plan and control their activities to achieve specific goals. They include increasing the efficiency of operations, increasing the total value of the enterprise, ensuring the growth of the welfare of shareholders and owners, maximizing financial results, minimizing losses, ensuring long-term liquidity and financial stability, as well as implementing a financial control policy. Controlling, unlike other management systems, covers the entire process of enterprise management, starting with the formulation of strategy, development of plans and budgets, and ending with the analysis of deviations of actual results from the set goals of the enterprise. To improve the formation and functioning of the financial controlling system, it is advisable to introduce a balanced system of indicators. It allows to identify and correct weak points in the economic activity of the enterprise, to find out the possibility of preventing the deterioration of the financial condition, to determine the main reasons with the help of cause-and-effect relationship of financial indicators, to improve investment and innovation activities. The purpose of the article is to substantiate the expediency of implementing a financial controlling system at the enterprise in modern business conditions. The article developed a system of balanced indicators for «HSMEP» LLC. Based on the analysis, it was determined that the concept of value-oriented enterprise management should be implemented at the enterprise of «HSMEP» LLC. This will allow you to get an effective management method, with which you can improve planning, increase the efficiency of operations, as well as the ability to achieve a gradual increase in the value of the enterprise. Such a management system will make it possible to bring corporate management to a higher and more modern level. Calculated level scientific and practical effectiveness implementation of the balanced scorecard is 56%. This indicates a sufficient level of effectiveness of the provided recommendations and proposals, which provide an opportunity to improve the indicators of the company's financial condition and ensure its competitiveness both on the Ukrainian and international markets.